PENGARUH FINANCIAL LITERACY DAN FINANCIAL SELF EFFICACY TERHADAP PERILAKU KEUANGAN DIMEDIASI OLEH SIKAP KEUANGAN PADA UKM KOTA MAKASSAR - Rischa Aulya Alam; Syamsu Alam; Mursalim Nohong (Scientium Management Review, 2022)
Small Medium Enterprises in Makassar city still need to gain their knowledge and understanding of financial literacy, financial self-efficacy, financial attitudes, and financial behavior toward SMEs industry. The Financial attitude decisions of each SME actor dominate financial literacy and financial self-efficacy in SME players in Makassar city. This study aims to analyze the effect of financial literacy and financial self-efficacy on Financial Behavior mediated by financial attitudes in SMEs in Makassar city. The method used in this research is a descriptive research method using a quantitative approach. The approach used is quantitative with a descriptive method. The research instrument used a questionnaire given to one hundred SMEs. Data were analyzed using regression analysis and path analysis. The study's results found that financial literacy did not positively and significantly affect financial attitudes in SMEs in Makassar City. Financial self-efficacy has a positive and significant effect on Financial attitudes. Financial literacy has a positive and significant effect on financial behavior. Financial Self Efficacy has no positive or significant effect on financial behavior. Financial attitude has a positive and significant effect on financial behavior. Financial attitude cannot mediate the effect of financial literacy on financial behavior. Financial attitudes can mediate the effect of financial self-efficacy on financial behavior. This research can support research progress within the scope of SMEs in Makassar city, especially in increasing the understanding of Makassar city SMEs finances.